2022
DOI: 10.3386/w30533
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Income on the Economic Wellbeing of Families with Low Incomes: Evidence from the 2021 Expanded Child Tax Credit

Abstract: We examine the effects of an unconditional cash transfer on the economic wellbeing (material hardship, ability to meet needs, money on hand, use of friends and family for assistance, and employment) of families and children with very low incomes. We use a parameterized differencein-differences approach to study the impact of the 2021 temporary expansion of the Child Tax Credit (CTC), which provided monthly, unconditional cash payments to families with children from July to December 2021. The 2021 monthly CTC r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…Comparing the results of the analyses using 2022 and 2019 ASEC data reveals that income support policies enacted in relation to the COVID-19 pandemic may have affected poverty risk in the U.S. For example, we estimated that using 2019 data 13% of individuals experienced poverty under the absolute threshold and 18% experienced poverty under the relative threshold, while using 2022 data the corresponding estimates were 8% and 15%. These findings are consistent with other research that examined the effect of pandemic-era policies, including stimulus checks, enhanced unemployment insurance, the expanded child tax credit, and SNAP emergency allotments, and concluded that they reduced poverty [ 37 , 50 53 ].…”
Section: Discussionsupporting
confidence: 90%
“…Comparing the results of the analyses using 2022 and 2019 ASEC data reveals that income support policies enacted in relation to the COVID-19 pandemic may have affected poverty risk in the U.S. For example, we estimated that using 2019 data 13% of individuals experienced poverty under the absolute threshold and 18% experienced poverty under the relative threshold, while using 2022 data the corresponding estimates were 8% and 15%. These findings are consistent with other research that examined the effect of pandemic-era policies, including stimulus checks, enhanced unemployment insurance, the expanded child tax credit, and SNAP emergency allotments, and concluded that they reduced poverty [ 37 , 50 53 ].…”
Section: Discussionsupporting
confidence: 90%
“…Second, we find that the expanded CTC contributed to higher average spending levels at personal care establishments, restaurants, and grocery and general stores. The latter finding is consistent with evidence that the CTC expansion reduced food hardship among families with children Pilkauskas et al, 2022). Notably, we do not find consistent evidence of greater consumption at alcohol, tobacco, or gambling establishmentseither on the extensive or intensive marginas a result of the CTC expansion.…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, we find that a $1,000 increase in annual income due to the CTC led to a 6.7 percent increase in visits to child care centers. Though an analysis of labor supply decisions is beyond the scope of this study, it is possible that these findings could contribute to explaining the expanded CTC's lack of negative employment effects in 2021 (Ananat et al, 2022;Pilkauskas et al, 2022). More broadly, the patterns suggest that an unconditional cash allowance could enable some parents to increase their labor supply, even as others may decrease it due to reduced employment incentives (National Academy of Sciences, 2019).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Examples of studies examining the effects of income on hardships other than food hardship include Pilkauskas & Michelmore (2019), who found that a $1,000 increase in the EITC reduced housing hardship (e.g., moderate or severe housing cost burdens and doubling up), and McKernan et al (2018), who examined the effects of SNAP, TANF, and public health insurance on aggregate hardship measures and found that participation in these programs reduces the total number of hardships that low-income families face by 48 percent. A more recent study by Pilkauskas et al (2022) examines the effects of the monthly CTC payments on a sample of families with very low incomes and found that the payments reduced the number of hardships faced and their levels of food insecurity. However, to date there are no studies examining the impact of the monthly CTC on a comprehensive set of hardships nor on any aggregate hardship indicators (e.g., experiencing multiple forms of hardship) in a representative sample.…”
Section: Materials Hardshipmentioning
confidence: 99%